KONTRIBUSI IBNU KHALDUN DALAM HISTORIOGRAFI ISLAM - Maryam Maryam (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
This article discusses the contribution of Ibnu Khaldun for the writingof Islamic history. The theme is still considered important in light of efforts toreconstruct the sequence of events of Islamic history still required to be done forthe needs of the present time. This study is based on the research literature ofIbnu Khaldun's writings and other writings that are relevant. The results of thissimple study show that the figure of a medieval historian has a very valuablecontribution to the preparation of the next Islamic history. He has made a sharpcriticism to the mistakes of the previous writing on Islamic history and offers theessential principles for further reforms of Islamic history writing.